Leadership through people skills - Lefton, Robert Eugene (New York Mcgraw-Hill, 2004)
Robert Lefton and Victor Buzzotta, cofounders of Psychological Associates, have revolutionized managerial procedure with their Dimensional Model--a behavioral standard that has been adapted and imitated by companies all over the world.
Includes bibliographical references (p. 227-230) and index.
Keywords: Leadership